STRATEGI GURU DALAM MENINGKATKAN KETERAMPILAN MENULIS CERITA NON FIKSI SISWA MI KHADIJAH KLOJEN MALANG - Fahimatud Diniyyah; Anwar Sa’dullah; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
With the advancement of the world of education in development to create a better learning process. Not only that, students are also expected to be more active in their opinions, gather new information and discuss so that they can come up with ideas to be able to hone their writing skills. In education also very much needed the role of a teacher as a professional educator, material that is in accordance with the needs, strategies or methods that are appropriate to achieve its objectives, there is an evaluation as a measuring tool to determine the ability and infrastructure to be able to support learning activities. At MI Khadijah Klojen the teacher's effort in improving students' writing skills using direct learning strategies (direct instruction), using lecture, question and answer, assignment and drill methods. And the teacher provides madding in each class. With this strategy, it is expected to improve the learning outcomes of students' writing skills at MI Khadijah Klojen.